2008
DOI: 10.1007/s00431-008-0727-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulse methylprednisolone with gammaglobulin as an initial treatment for acute Kawasaki disease

Abstract: Approximately 15-20% of patients with Kawasaki disease (KD) are not responsive to high-dose intravenous gammaglobulin (IVIG). We have previously reported a predictive method for identifying IVIG-non-responsive patients (high-risk KD patients). We determined the safety and effectiveness of pulse methylprednisolone with high-dose IVIG (mPSL+IVIG) as a primary treatment for high-risk KD patients. Sixty-two high-risk KD patients were treated with pulse methylprednisolone 30 mg/kg over 2 h, followed by IVIG 2 g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 12 publications
3
91
2
Order By: Relevance
“…28 Okada et al also showed that methylprednisolone + IVIG is effective and safe as a primary treatment for high-risk KD patients. 29 However, Newburger et al's data do not provide support for the addition of a single, pulsed dose of intravenous methylprednisolone to conventional IVIG therapy as routine primary treatment of children with KD. 30 The usefulness of steroids in the treatment of KD is not well established.…”
Section: Discussionmentioning
confidence: 98%
“…28 Okada et al also showed that methylprednisolone + IVIG is effective and safe as a primary treatment for high-risk KD patients. 29 However, Newburger et al's data do not provide support for the addition of a single, pulsed dose of intravenous methylprednisolone to conventional IVIG therapy as routine primary treatment of children with KD. 30 The usefulness of steroids in the treatment of KD is not well established.…”
Section: Discussionmentioning
confidence: 98%
“…In these patients, CALs frequently developed, despite the use of additional treatments, including further IVIG and steroids, thus indicating that current alternative treatments are ineffective after the failure of the initial IVIG treatment (4 -6). In other words, an earlier and more effective primary therapy is required for IVIG-resistant patients (7)(8)(9)(10)(11). Steroid therapy has been reconsidered as a therapeutic strategy to treat KD (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In other words, an earlier and more effective primary therapy is required for IVIG-resistant patients (7)(8)(9)(10)(11). Steroid therapy has been reconsidered as a therapeutic strategy to treat KD (11)(12)(13)(14)(15). A novel therapeutic approach may not be necessary in all cases of KD because the appropriate dose of IVIG and aspirin yields a good response in 80 to 85% of patients.…”
mentioning
confidence: 99%
“…The most utilized treatment is the application of Intravenous gammaglobulin (GGIV) at a dose of 2 per kg in a sole dose for a 12-infusion; this is the most accepted treatment and has allowed to the reduction of prevalence of aneurysms to <5% and a mortality of 2% to 0.3%, although the GGIV scheme is at a dosage of 400 mg × kg × day for 5 days, plus aspirin at 80 to 100 mg × kg × day. According to response, the GGIV dose can be repeated, or corticoids can be added, especially in refractory cases (Cha, 2008;Chung, 2009;Falcini, 2006;Hung, 2009;Miura, 2008;Newbauer, 2004;Ogata, 2009;Okada, 2009;Sano, 2010;Tremoulet, 2008).…”
Section: Treatmentmentioning
confidence: 99%
“…Concerning recommendation for treatment of KD during the past 3 years, it as been mentioned that the greatest effectiveness in cases of relapse or resistance is obtained on utilizing pulses of methylprednisolone in addition to GG. In cases of recurrence of fever or resistance to GGIV, this combination has even been recommended as initial therapy (Cha, 2008;Chung, 2009;Miura, 2008;Ogata, 2009;Okada, 2009;Sha, 2008). Cardiovascular sequelae of KD in the adult in Japan.…”
Section: Treatmentmentioning
confidence: 99%